p53-Induced LINC00893 Regulates RBFOX2 Stability to Suppress Gastric Cancer Progression - Ou, Xinde; Zhou, Xingyu; Li, Jin; Ye, Jinning; Liu, Haohan; Fang, Deliang; Cai, Qinbo; Cai, Shirong; He, Yulong; Xu, Jianbo (Frontiers in Cell and Developmental Biology, 2022)
Long noncoding RNAs (lncRNAs) have been reported to regulate diverse tumorigenic processes. However, little is known about long intergenic non-protein coding RNA 00893 (LINC00893) and its role in gastric cancer (GC). Herein we investigated its biological functions and molecular mechanism in GC. LINC00893 was decreased in GC tissues but significantly elevated in AGS cells after treatment with Nutlin-3. In GC patients, it was found that low expression of LINC00893 was correlated with tumor growth, metastasis and poor survival. Functionally, overexpression of LINC00893 suppressed the proliferation, migration and invasion of GC cells. Mechanistically, LINC00893 regulated the expression of epithelial-mesenchymal transition (EMT)-related proteins by binding to RNA binding fox-1 homolog 2 (RBFOX2) and promoting its ubiquitin-mediated degradation, thus suppressing the EMT and related functions of GC. In addition, the transcription factor p53 can regulate the expression of LINC00893 in an indirect way. Taken together, these results suggested that LINC00893 regulated by p53 repressed GC proliferation, migration and invasion by functioning as a binding site for RBFOX2 to regulate its stability and the expression of EMT-related proteins. LINC00893 acts as a tumor-inhibiting lncRNA that is induced by p53 in GC and regulates EMT by binding to RBFOX2, thus providing a novel experimental basis for the clinical treatment of GC.